THE DECLINE IN BUMDes PERFORMANCE DURING THE COVID-19 PANDEMI (EVALUATION OF ENVIRONMENTAL TURBULENCE IN THE FUTURE) - Linda, Linda; Ismaulina, Ismaulina; Febriyanty Lautania, Maya (J-ISCAN: Journal of Islamic Accounting Research, 2023)
This study aims to analyze the causes of the decline in the performance of BUMDes in the city of Banda Aceh during the Covid-19 pandemi. Environmental turbulence or external conditions that lead to opportunities or threats to business continuity. The results of previous studies showed that the financial performance of BUMDes during the Covid 19 pandemi experienced a very drastic decline and many BUMDes went bankrupt because they were unable to compete in the market. The exogenous variables in this study are environmental turbulence and working capital. The endogenous variables are transparency and falling BUMDes financial performance, where the transparency variable is an intervening variable. Analysis of the influence of exogenous variables on endogenous variables using SEM-PLS with the study population being BUMDes administrators in the city of Banda Aceh. Respondents in the study were chairmen, secretaries and treasurers of BUMDes who were active in the city of Banda Aceh The results showed that the environmental turbulence and working capital variables through the transparency variable had a significant negative effect on the fall in BUMDes financial performance during the Covid 19 pandemi. Which means that environmental turbulence caused a fall in BUMDes financial performance. These findings show the importance of BUMDes to carry out various product innovations when environmental turmoil occurs so that their business can be sustainable.